Analysis of Determinant Factors of Low Exclusive Breastfeeding Practice in Urban Slum Community of Surabaya - Hanna Tabita Hasianna Silitonga; Abigail Elsha Tiara Susanto; Nadya Refina Tiurlan Barasa (Faculty of Medicine, Public Health, and Nursing, 2019)
Background: The World Health Organization’s recommendation for infant feeding is exclusive breastfeeding for the first six months followed by semi-solid food. The purpose of the study is to analyse determinant factors related to low exclusive breastfeeding’s practice in the urban slum community of Surabaya. Methods: This is a qualitative study with a case study in one of the urban slum areas of Surabaya. Data were collected by in-depth interviews and focus group discussion (FGD) with mothers, interviews with key-informants; posyandu cadre and the community leader for validation. Ishikawa diagram tool was used to identify and categorize determinant factors. The Urgency, Seriousness, Growth (USG) method was used to prioritize factors.Results: There are 9 determinant factors categorized into 5 categories; two ‘main’ factors, three ‘method’ factors, two ‘material’ factors, one ‘money’ factor and one ‘environment’ factor. The one factor that was considered the priority to be resolved is from the environment factor that is local beliefs of breastfeeding and expressed breast milk.Discussions and Conclusions: Education of mothers about expressed breast milk is an initial step to overcome low exclusive breastfeeding’s practice in this community due to mothers having to work outside the house. There is also a need for strengthening support groups so working mothers continuously exclusive breastfeed and provide optimal nutrition for infants.